CONTEMPORARY LEGAL APPROACHES FOR TECHNOLOGICAL DEVELOPMENT - Azevedo, Isabelle Cristinne Alves; Rocha, Guilherme Ribeiro; Santana, Guilherme Saldanha; dos Santos, Diogo de Almeida Viana (Seven Editora, 2026)
Technological development simultaneously drives economic advancement and generates challenges that often exceed the regulatory capacity of existing legal systems. Grounded in critical theoretical perspectives, the paper rejects the notion of neutral technological progress and emphasizes the role of power structures and institutional choices in shaping technological trajectories and their social consequences. Drawing on an interdisciplinary theoretical framework that integrates the political economy of technological progress, legal theory, and methodological approaches to legal research, this study aims to understand key events of the Digital Revolution, the role of integrating different methodological approaches, and to contribute to a more flexible, responsive, and technologically compatible legal approach aligned with the dynamics of contemporary technological development.